2011
DOI: 10.2304/pfie.2011.9.5.573
|View full text |Cite
|
Sign up to set email alerts
|

A Path Analysis Study of School Culture and Teachers' Organisational Commitment

Abstract: In this study, the direct and indirect relations between school culture and the organisational commitment of primary school teachers were analyzed. The subjects of the research consisted of primary school teachers who worked at a district in Istanbul in the academic year 2007-2008. The sampling group was defined by the cluster sampling method. In total 200 teachers participated. Two scales were used to collect data, the organisational commitment scale (OCS) and the school culture scale (SCS). Linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…In accordance with the previous evidence that teachers often move to schools with better working conditions, this study found that the teachers from the schools with insufficient resources and supports, and unsatisfactory school climate, were more likely to leave (Allensworth et al., 2009; Karadag et al., 2011). The organizational conditions, such as the teaching hours, teacher collaboration, teacher–student relationships, and school discipline, all influenced teachers’ transfer intentions.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with the previous evidence that teachers often move to schools with better working conditions, this study found that the teachers from the schools with insufficient resources and supports, and unsatisfactory school climate, were more likely to leave (Allensworth et al., 2009; Karadag et al., 2011). The organizational conditions, such as the teaching hours, teacher collaboration, teacher–student relationships, and school discipline, all influenced teachers’ transfer intentions.…”
Section: Discussionsupporting
confidence: 90%
“…The school culture and values that exist within the organization affect the degree of the teacher's emotional identification with the school. (Finegan, 2000;Karadac, Baloglu & Cakir, 2011).  trust and expectations.…”
Section: The Organizational Commitment Of Teachersmentioning
confidence: 99%
“…The results of this study implies that teachers who have positive attitude towards the teaching profession, positive beliefs about students' learning, positive value systems and are serving in an institution with excellent school culture, tend to be more committed in the teaching profession. Karadag, Baloglu and Cakir (2011) analyzed direct and indirect relations between school culture and the professional commitment of primary school teachers in Turkey. The findings indicated that although there was a positive correlation between school culture and professional commitment, the direct effect of school culture on professional commitment was not meaningful.…”
Section: Research Objectivementioning
confidence: 99%